Investigating a comprehensive model for evaluating occupational and environmental risks of dimensional stone mining (Rudarsko-geološko-naftni zbornik, 2020)
One of the most hazardous fields of engineering is mining operations and accordingly, it requires extra consideration on risk evaluation. Decorative stone quarrying is one of the main branches of the mining industry in Iran. Currently, Iran, China and Italy are known as the three main producers of decorative stones in the world. Subsequently, risk assessment is one of the main steps of quarrying organization. One of the main steps of risk assessment is Risk Breakdown Structure (RBS). In order to achieve this goal, a comprehensive structure of dimensional stone quarrying is modelled in this re- search and divided into 17 main levels. One of the most useful procedures of risk ranking is Multi attribute decision- making methods which state that they have numerous affecting parameters. In the next step of this study, the main hazards of main decorative stone quarrying are assessed by implementing the ‘Preference Ranking Organization Method for Enrichment Evaluation’ (PROMETHEE) technique. As a final point, Economical, Management, and Schedule risks are determined as the most intimidating hazards in this field.